Security-constrained hybrid optimal energy flow model of multi-energy system considering N-1 component failure. (1st August 2023) - Deng, Jingwei; Wu, Gang; Wang, Yang; Su, Yunche; Liu, Aifeng
Abstract: The analysis and calculation of hybrid energy flow is the basis of planning, operation and market transaction of multi-energy systems. An optimal energy flow model of multi-energy systems considering N -1 component failure is proposed in this paper. The compressor and gas storage devices are modeled in the hybrid optimal energy flow model. The particle swarm intelligent optimization algorithm is used to solve this non-convex and non-linear optimization model. Case studies demonstrate the coupled and complementary operation of multi-energy systems can reduce the total operation cost by 8 % as compared to independent operation model. The hybrid optimal energy flow (HOEF) model of multi-energy systems with N- 1 component failure can improve the robustness of HOEF results. Graphical abstract: Research architecture diagram of this paper. Unlabelled Image Highlights: A hybrid optimal energy flow model is proposed. The N -1 security analysis is considered. The gas storage and compressor are considered.